SEJARAH PERTUMBUHAN DAN PERKEMBANGAN PARTAI MASYUMI (1945-1960) - Insan Fahmi Siregar (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
The Masyumi Party is one of the political parties emerging from theproclamation of Indonesian Independence Day. It was the only party during the early days of independence which was grounded upon Islamic principle. It had been the biggest political party until the early 50s. That position changed, however, after Nahdhatul Ulama left in 1952 and the Masyumi Party became the second largest. The number of its members declined during the transitional period from parliamentary to guided democracy and continued to fall after the special membership of Masyumi was removedin 1959. This party was finally dispersed in 1960.Keywords: Partai Masyumi, demokrasi, NU, Muhammadiyah